The Effects of Monetary Variables on the Growth of Small and Medium Industry in Aceh Province - Ade Habya Fijay; Vivi Silvia; Chenny Seftarita (International Journal of Quantitative Research and Modeling, 2021)
This study aims to analyze the effect of inflation, bank credit, and SMI investment on the growth of small and medium industries in Aceh Province. This study uses panel data consisting of 23 districts/cities in Aceh Province during the period 2014 to 2020. The analysis model used in this study is a panel data regression model. The results found in this study are variables that have a significant effect on the growth of SMIs in Aceh Province are inflation and investment in SMIs. Meanwhile, the banking credit variable has not had a statistically significant effect on the growth of SMIs. The inflation variable has a negative and significant effect on the growth of SMIs so that uncontrolled inflation will have a negative impact on the growth of SMIs. Meanwhile, SMI investment has a positive and significant impact on the growth of SMIs so that various targeted investment policies are needed so that they can support the development of SMIs in Aceh Province.